ANALISIS TINGKAT KEVALIDAN MEDIA KUIS INTERAKTIF BERBASIS KAHOOT UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS MATERI GAYA DI SEKITAR KITA KELAS IV SD - Maryana Salsabila; Sumadi; Ina Agustin (Universitas Negeri Medan, 2026)
This study aimed to determine the validity level of Kahoot-based interactive quiz media in science and social studies (IPAS) learning on the topic of forces in everyday life for fourth-grade elementary school students. The study was motivated by low student engagement and learning outcomes caused by less interactive learning media. This research used the Research and Development (R&D) method with the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The subjects included material experts, language experts, media experts, and fourth-grade students. Data were collected through observations, interviews, and validation questionnaires, then analyzed using descriptive quantitative techniques. The results showed validation percentages of 93% from material experts, 97% from language experts, and 96% from media experts, all categorized as very valid. These findings indicate that the developed media has met the aspects of material suitability, language, visual appearance, and learning interactivity. Therefore, the Kahoot-based interactive quiz media is appropriate for use in IPAS learning to support students learning outcomes.